Transformation of Education Processes and Preparation of Competencies for the Digital Economy - Kosenchuk, Olga V.; Kulapov, Mikhail N.; Diner, Yuliya A.; Zinich, Alla V.; Revyakina, Yulia N.; Adelfinskiy, Alexey O. (International Journal of Criminology and Sociology, 2021)
In this article, the problem of training specialists with digital competencies for the agricultural sector, as the main industry, necessary for the food security of the state. The analysis of the views of researchers on the issues of teaching youth in the context of global digitalization is presented. The analysis and generalization of information about modern technologies in the system of training personnel for the agro-industrial complex, taking into account the experience of the Omsk State Agrarian University, with the support of modern information and communication technologies. The idea is substantiated that digitalization of production and management processes in the agro-industrial complex is impossible without hard and soft skills with new competencies. The article summarizes new material based on the results of a survey of rural youth in Russia and Kazakhstan on the problem of professional self-determination. The characteristic features of modern students and their self-positioning in the conditions of a changing professional environment are highlighted and described. Special attention in the work of the authors is focused on the need to form an educational trajectory, which is based on the symbiosis of classical agricultural education, practice-oriented learning, project activities, concepts - technologies, e-learning and other digital educational resources. The conclusion reveals the authors' opinion on the forecast trends on the issue under study.